Identification and Hierarchy of Traditional Village Characteristics Based on Concentrated Contiguous Development—Taking 206 Traditional Villages in Hubei Province as an Example - Xiaohu Liu; Lei Yuan; Gangyi Tan (Land, 2023)
Public policy for the preservation and development of traditional villages in China has witnessed a shift. That is from the equal distribution of finances to officially recognised traditional villages to the prioritisation of the development of more potential traditional villages that stimulate the development of surrounding villages and regions. This study takes 206 traditional villages in Hubei Province as an example and proposes a method framework for ‘Feature identification, Hierarchical classification (FIHC) that combines field research, spatial geography and spatial network methods. The results of spatial geography show that traditional villages in Hubei province are unevenly distributed, mainly along the mountain ranges in the east and west, with scattered distribution in the central plains. The kernel density result reveals “3 + 2 high-density hotspot zones” (A, B, and C are high-density areas, whereas D and E are low-density areas). Furthermore, the results of the spatial network appear that the traditional villages’ ecological situation in Zone A is better than in other areas, but their transportation accessibility and economy are poor; Zone B villages’ transportation accessibility is better than in other areas; Zone C has the best economy; and three conditions of traditional villages in the D and E zones are poor. FIHC can identify villages with more development potential and stratify these villages in a multidimensional way. It is innovative and an important contribution to policymakers and planners in developing ‘phased and focused’ public policies and rural planning.